Strategi Pengembangan Usaha Pengolahan Gula Aren Perspektif Ekonomi Islam di Desa Kandang Mbelang Kec. Lawe Bulan, Kab. Aceh Tenggara - Ulfa Yolanda (Jurnal Ilmiah Ekonomi Islam, 2023)
Sem business competition will rapidly encourage every palm sugar manager to have strategic acumen, so that he excels in competing with his competitors or at least is able to survive to run his business. Therefore, palm sugar managers are not only looking for profit, but are also connected with moral values, it is not justified to take maximum profits without regardto the buyer's condition, as Islam emphasizes that in business trading must be honest, trustworthy, fair and also pay attention to The quality of the raw material for palm sugar must be guaranteed to be halal, for the sake of creating human happiness (falah) and a good life. This study aims to analyze the opportunities and development of the palm sugar business in Kandang Mbelang Mandiri Village, Kec. Moonstone, Kab. Southeast Aceh. The respondents of this study were entrepreneurs managing palm sugar in the village of Kandang Mbelang. Research data obtained by observation and interviews were analyzed descriptively using SWOT analysis, strategy matrix to analyze the strategy determined by the respondents. The results of this study indicate that the IFAS value is 1.447320 and the EFAS value is 2.261670. Therefore the solution obtained for the development of the palm sugar business is to promote products such as on social media, have a brand image, innovate the quality of palm sugar products in the future.